Heteroannulation Reaction of α-Aminoketones for the Efficient Synthesis of 4-Imidazolin-2-ones and 2-Thiones - Rebollar,Araceli (2022)
The hydrogenation of α-oximinoketones in methanol/HCl afforded α-aminoketones, which were applied without purification to the synthesis of 4-imidazolin-2-ones and 2-thiones, including chiral derivatives. The latter two series were obtained in high yields by a heteroannulation reaction of α-aminoketones with isocyanates and isothiocyanates, respectively. A double condensation of the α-aminoketones with two mol equivalents of the isocyanates produced a series of 4,5-dialkyl-N,3-diaryl-2-oxo-2,3-dihydro-1H-imidazole-1-carboxamides. With isothiocyanates, a single condensation reaction furnished a series of 4,5-dialkyl-1-aryl-1H-imidazole-2(3H)-thiones, which underwent alkylation with alkyl halides to form the corresponding 1-aryl-2-thioalkyl-1H imidazoles in high yields.